Peer victimization in early adolescence and maladjustment in adulthood - Kretschmer, Tina; van der Ploeg, Rozemarijn; Kaufman, Tessa (European Child & Adolescent Psychiatry, 2024)
Studies report different effect sizes for associations between peer victimization and later maladjustment. A possible origin of this heterogeneity is the length of the interval between victimization and maladjustment assessments. Effect sizes might also vary as a function of reporter. Longitudinal data from TRAILS, a study of adolescents followed from age 11 to 29 (baseline n = 2229) were used to test whether peer victimization assessed from adolescents themselves, their parents, teachers, and peers predicted internalizing symptoms, thought problems, and somatic complaints at six follow-ups with a temporal distance of up to 19 years. Neither self- nor peer-reported victimization predicted later maladjustment. In contrast, parent-reported victimization stably predicted adult maladjustment. Teacher-reported victimization also predicted maladjustment but associations were weaker and largely non-significant when parent reports were accounted for simultaneously. Parent-reported peer victimization has traditionally played a minor role in bullying research as parents are usually not present when victimization occurs. The results of this study however suggest that parents should be listened to when talking about their offspring being victimized.
CRIS-Team Scopus Importer:2025-03-19
Keywords: Bullying-victimization; Longitudinal; Mental health